Microbial quality assessment of Niger seed (Guizotia abyssinica (Linnaeus f.) Cassini) oil in Gondar city: A laboratory-based cross-sectional study - Lamrot Yohannes; Tsegaye Adane Birhan; Mastewal Endalew; Jember Azanaw; Fasika Weldegebrel (PLoS ONE, 2025)
Foodborne diseases pose a significant public health challenge worldwide. The increasing availability of edible oils in the market, combined with Ethiopia’s lack of stringent quality control and regulatory oversight, raises concerns about their safety. This inadequacy in regulation may contribute to microbial contamination, leading to potential public health risks. A laboratory-based cross-sectional study was conducted from May to July 2021. Twelve samples of Niger seed oil (Guizotia abyssinica (Linnaeus f.) Cassini) were collected using a universal sampling technique. In the microbiology laboratory, the samples were aseptically examined for bacterial and fungal contamination using standard microbiological methods and procedures. The collected data were entered and analyzed using Stata Version 14. Mean values and standard deviations were computed, and the results were presented in text and tables. Microbial analysis of the 12 Niger seed oil (Guizotia abyssinica (Linnaeus f.) Cassini) samples revealed varying levels of bacterial, mold, and coliform contamination. The identified bacterial species included Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa, while Aspergillus niger, Aspergillus flavus, and Aspergillus fumigatus were the predominant fungal isolates. The total aerobic bacterial count ranged from 1.3 × 103 to 9.2 × 104 cfu/ml, with the highest recorded mold count reaching 4 × 10⁵ cfu/ml. Additionally, both total and fecal coliform isolates were detected in the samples. The presence of these microorganisms suggests that the oil processing, production, handling, and storage systems lack proper hygienic handling practices. This finding highlights the urgent need for stringent hygiene measures, enhanced quality control protocols, and strict adherence to food safety regulations throughout the production and distribution processes.